2012
DOI: 10.1016/j.jmb.2012.04.024
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Sec13/31 COPII Cage Bound to Sec23

Abstract: Structural studies have revealed some of the organizing principles and mechanisms involved in the assembly of the COPII coat including the location of the Sec23/24 adapter layer. Previous studies, however, were unable to unambiguously determine the positions of Sec23 and Sec24 in the coat. Here we have determined a cryogenic electron microscopic structure of Sec13/31 together with Sec23. Electron tomography revealed that the binding of Sec23 induces Sec13/31 to form a variety of different geometries including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 32 publications
4
38
0
Order By: Relevance
“…This same study also revealed that the Sec23/24 cargo adaptor assembled into a regular lattice on the membrane surface [48] . Taken together, the findings from this and earlier work [43, 44, 49, 46, 47] indicate that the COPII coat can adopt a variety of geometries to accommodate a range of vesicle sizes, with the Sec23/24 adaptor itself playing an unexpected structural role in determining vesicle shape [48] .…”
Section: Copii Coat Assembly May Accommodate Different Cargo Sizessupporting
confidence: 58%
“…This same study also revealed that the Sec23/24 cargo adaptor assembled into a regular lattice on the membrane surface [48] . Taken together, the findings from this and earlier work [43, 44, 49, 46, 47] indicate that the COPII coat can adopt a variety of geometries to accommodate a range of vesicle sizes, with the Sec23/24 adaptor itself playing an unexpected structural role in determining vesicle shape [48] .…”
Section: Copii Coat Assembly May Accommodate Different Cargo Sizessupporting
confidence: 58%
“…Several lines of evidence indicate that the COPII cage is flexible 35,36 , and this would allow the formation of larger COPII-coated intermediates and thereby the transport of large cargo. A combination of structural approaches has revealed that SEC13–SEC31 subunits can self-assemble into polyhedral cages of distinct orders through moderate variation in geometries of subunit interactions 3739 (FIG. 2).…”
Section: Mechanisms Of Interface Controlmentioning
confidence: 99%
“…c | The structures for the SEC13–SEC31 assembly unit 38 and the SEC13–SEC31 cage 37 in the presence of SEC23 (REF. 147) and SEC23–SEC24 (REF. 35) have been reported.…”
Section: Figurementioning
confidence: 99%
“…Subsequently, it recruits Sec23/24 heterodimer via specific interactions with Sec23 to form 'prebudding' complex (23,24) in which cargo is captured by Sec24 (25,26). Eventually, Sec13/31 heterotetramer is recruited that drives the membrane deformation and stimulates the GAP activity of Sec23 towards Sar1 resulting in the release of cargo containing COPII coated vesicles from the ER membrane (27)(28)(29). However, COPII complex and its role in the secretory pathway in Leishmania is not known.…”
Section: Introductionmentioning
confidence: 99%